The Role of the Marindal 1 Village Government, Patumbak District in Local Development: Facing Current Challenges - Pangaribuan, Margaret; Meliana, Riomas; Marbun, Tasya; Purba, Widya; Halking, Halking (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This research aims to dig deeper into the role of the Marindal 1 Village government in local development, especially in facing current challenges. By collecting data from village officials and local communities, this research will provide a complete picture of strategies, obstacles and opportunities in building competitive and sustainable communities.